Cellulose powder from Piper nigrum L. agro-industrial waste: effect of preparation condition on chemical structure and thermal degradation - Ain Nadiah Sofiah Ahmad Khorairi; Noor Soffalina Sofian-Seng; Rizafizah Othaman; Khairul Farihan Kasim (Penerbit Universiti Kebangsaan Malaysia, 2020)
White pepper is generally produced via water retting process to decorticate the pericarp of green pepper. The decorticated pericarp is considered as an agro-industrial waste and environmental pollutant as many farmers still discard the waste into the rivers. These wastes majorly contain cellulose, hemicellulose, pectin, and other organic compound. Cellulose was obtained from alkaline treatment (4 wt. % sodium hydroxides, NaOH) followed by bleaching process. This study reports the effect of soaking cycle in bleaching treatment on the chemical structure and thermal degradation of cellulose. The cellulose obtained from pepper (Piper nigrum L.) pericarp waste were characterised by colour analysis, Fourier transform infrared spectroscopy (FTIR) and thermogravimetric analysis (TGA). Increased number of bleaching cycles produced a whiter colour and high thermal stability of cellulose powder. The whiteness index (WI) for high bleaching cycle sample was found significantly high (p<0.05) with the value of 77.00 ± 1.10. Thermal analysis indicates a derivative thermogravimetric analysis (DTG) peak at 332 °C. The FTIR spectrum proven that the condition of bleaching treatment changes the absorption intensity at bands 1732, 1540, and 1460 cm-1 which due to the loss of hemicellulose and lignin. The use of pepper pericarp waste that is usually discarded may provide a sustainable alternative for the production of cellulose.